Subchronic Toxicity Test of Kebar Grass Extract of n-Hexane (Biophytum Petersianum Klotzsch) on Weight, ADG and Vital Organ Weight of Rat (Rattus Norvegicus) - Sambodo, Priyo; Nurhayati, Dwi; Purwaningsih, Purwaningsih; Susmiati, Trini; Airin3, Claude Mona (Journal of Food and Pharmaceutical Sciences, 2018)
The recent study was carried out to determine the effect of Kebar grass extract of N-hexane (Biophytum petersianum Klotzsch) for 28 days peroral on weight, ADG and weight of vital organs of white rat. Forty male and female rats of Sprague Dawley strain aged 8 weeks were examined. The formulated rats were divided into four groups, group I (control), group II, III, IV (treatment), in which each consisted of five rats. The feed were given as much as 15 g/rat/day, while drinking ad libitum. In the control group, the rats were given solvent extract, group II, III and IV were given fraction of n-hexane of Kebar grass extract at 1 mg/kg BW, 5 mg/kg BW and 10 mg/kg BW peroral, respectively. Test preparation was given daily for 28 days, observation of toxic symptoms was performed every day while weighing was performed once every two weeks. Based on results obtained in this line of research, the findings indicated that Kebar extract administration for 28 days did not cause toxic symptoms in both male and female rats either in dose II, III or IV. Weight and ADG of male and female rats did not indicate significant differences between the control group and the treatment group. Keywords: kebar grass, rats, subcronic toxicity test, OECD 407